Legal Protection for Land Rights Holders in Land Disputes Over Customary Land Based on Girik Case Study of PK Decision Number 1169 Pk/Pdt/2023 - Firmansyah, Melania Indiana Putri; Handayani, Sri Wahyu (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
This thesis analyzes the complex land issues in Indonesia, particularly concerning adat land disputes based on girik ownership in the face of a dominant, centralized national land law system. As an agrarian nation with diverse traditional land ownership systems, Indonesia frequently encounters conflicts between adat rights and state or private interests. Girik, a traditional proof of land control, is often not fully recognized by the modern legal system, even though Law No. 5 of 1960 on Basic Agrarian Principles has accommodated ulayat rights. This research focuses on the dispute between Lumin Tuningtyas (girik holder) and Desyanto (Certificate of Ownership/SHM holder) in East Jakarta. The case highlights the discrepancy between customary law recognition and positive law. Lumin Tuningtyas filed a lawsuit based on inherited girik ownership, while Desyanto defended his ownership based on an SHM registered with the National Land Agency (BPN). Although the District Court initially granted part of Lumin Tuningtyas's claim, the decision was overturned at the appellate level, and the Supreme Court rejected Lumin Tuningtyas's cassation and judicial review (PK) requests. In its PK decision No. 1169 PK/PDT/2023, the Supreme Court affirmed that a certificate registered with the BPN is the legitimate proof of ownership, while girik is only considered proof of control. This ruling underscores the necessity of a multidimensional approach to adat land disputes, one that not only relies on positive legal instruments but also considers the historical, anthropological, and sociological aspects of indigenous communities. This thesis argues that court decisions, which tend to be centralized and state-oriented, need to be transformed into a legal paradigm that is more responsive to the rights of indigenous communities and the principle of substantive justice. This research aims to dismantle less responsive legal practices and encourage systemic change in handling land disputes in Indonesia, in order to uphold justice and build a more humane legal system.